2020
DOI: 10.1096/fj.202002108r
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of microRNA processing by 5‐lipoxygenase

Abstract: MiRNAs are a class of noncoding RNAs which modulate the expression of most of the human protein-coding genes by binding to specific target sites in the 3′ untranslated region of their target mRNA, resulting in degradation or translational repression. Their biogenesis is tightly regulated on multiple levels and dysregulation causes many human diseases. 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Gene encoding miRNAs is transcribed by RNA polymerase (Pol) II/III and processed via an evolutionarily conserved pathway [ 48 ] ( Figure 1(a) ). Specifically, a long primary transcript (pri-miRNA) shapes a characteristic hairpin structure that can be cleaved into a precursor miRNA (pre-miRNA) of approximately 60 nt in length by the microprocessor complex consisting of Drosha and DiGeorge syndrome critical region 8 (DGCR8) [ 49 ]. The produced pre-miRNA is then translocated to the cytoplasm via exportin 5 and Ran-GTP complex.…”
Section: Roles Of Main Noncoding Rnas In Cancermentioning
confidence: 99%
“…Gene encoding miRNAs is transcribed by RNA polymerase (Pol) II/III and processed via an evolutionarily conserved pathway [ 48 ] ( Figure 1(a) ). Specifically, a long primary transcript (pri-miRNA) shapes a characteristic hairpin structure that can be cleaved into a precursor miRNA (pre-miRNA) of approximately 60 nt in length by the microprocessor complex consisting of Drosha and DiGeorge syndrome critical region 8 (DGCR8) [ 49 ]. The produced pre-miRNA is then translocated to the cytoplasm via exportin 5 and Ran-GTP complex.…”
Section: Roles Of Main Noncoding Rnas In Cancermentioning
confidence: 99%
“…Biosynthesis of microRNAs is now described in detail and involves a series of sequential processes, including the formation of primary miRNA transcripts (pri-miRNAs) by RNA polymerase II, their subsequent cleavage in the nucleus by Drosha endonuclease to form pre-miRNAs. After transport into the cytoplasm, they are subsequently processed by a multiprotein complex, including Dicer [ 133 , 134 ].…”
Section: Role Of Micrornasmentioning
confidence: 99%
“…Interestingly, 5-LOX can modulate miRNA processing in monocytic cells. It has been shown that 5-LOX can interact with human Dicer [ 133 , 145 , 146 ]. Dicer, which is involved in microRNA biogenesis, is known to interact with cellular proteins through its N-terminal domain.…”
Section: Role Of Micrornasmentioning
confidence: 99%
“…Canonically, primary miRNAs (pri-miRNAs) are transcribed, which are further cleaved by Microprocessor comprised of RNase III enzyme DROSHA and DGCR8 to yield the pre-miRNAs. The pre-miRNAs are exported to cytoplasm where they were cleaved by DICER to generate mature miRNAs ( Spadotto et al, 2020 ; Uebbing et al, 2021 ). miR-214 is located in the DNM3OS transcript unit which gives rise to mature miR-214 ( Qin et al, 2012 ; Savary et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%